Loss Prevention and Safety Control: Terms and Definitions - Nolan, Dennis P (Occupational Safety and Health Guide Series, 2016)
An encyclopedic, A-Z listing of terminology, this book addresses the need for a reference that provides complete descriptions of the terminology used in the safety/loss prevention field. This text covers background, meanings, and descriptions of terms. It presents terminology in alphabetical order and contains supplemental appendices of safety organizations, common safety standards, and acronyms. Two-paragraph descriptions of terms, photographs, diagrams, graphs, and tables are included to aid understanding of the subject.